Silvicultural potential of two legume species in different planting spacing - Paulo André Trazzi; Marcos Vinicius Winckler Caldeira; Lucas Dambròz Beccalli; Rafaella de Angelli Curto; Ranieri Ribeiro Paula; Annanda Souza Campo; Rafael Barbosa Diogenes Lienard; Robert Gomes; Otracilio José Passos Rangel (Annals of Silvicultural Research)
The objective of this work was to investigate the silvicultural potential of angico (Anadenanthera peregrina (L.) Speg.) and paricá (Schizolobium parahyba var. amazonicum (Huber ex Ducke) Barneby)) in different planting spacings. The study evaluated the three spacings: 3 m x 3 m, 4 m x 4 m and 5 m x 5 m. A forest inventory was carried out eight years after planting in order to characterize the stand in terms of diameter at breast height (dbh), commercial height, total height and survival. Using dbh, height-diameter relationship and commercial volume models were adjusted for each planting spacing. A meta-analysis was conducted to compare the differences between results in the literature for species of the Fabaceae family. In both species, the 3 m x 3 m spacing produced the largest volumes and the 5 m x 5 m spacing the smallest volume. The angico recorded total mean volume ranging from 23.8 to 29.8 m³ per hectare. The paricá had total mean volume between 111.8 and 143.0 m³ per hectare. There was a strong correlation between height and dbh for the species in the meta-analysis. Higher mean height and dbh values were found for paricá when compared to the other Fabaceae species, showing the species' strong suitability for forestry.